Studi Komparatif Eropa dan Indonesia (Perbedaan pada Standar Akuntansi Pemerintah) - Ghina Adhha Haura; Ella Rahmayanti (Jurnal Penelitian Ekonomi Akuntansi, 2024)
Each country certainly has different Government Accounting Standards. This can be seen from the different forms of philosophy of each country, such as the state of the economy, social environment, culture, politics, law, and defense and security of each country. The process of modernizing public sector accounting is carried out intensively by stakeholders because there is a demand for high quality and relevant disclosures to decision making as financial information to meet transparency and accountability capabilities. The forms of accounting standards used by the public sector across Europe are heterogeneous or varied. Meanwhile, the Government of Indonesia began to fully enforce the Accrual-Based Government Accounting Standards for all local governments after the issuance of Government Regulation number 71 of 2010. The purpose of this comparative study is to examine the literature on the differences in Government Accounting Standards in member countries of the European Union and Indonesia. The benefits of this research are expected to provide comprehensive information regarding the description of Government Accounting Standards, especially in European Union countries and Indonesia. The results of this study are Government Accounting Standards in the European Union and Indonesia countries are very different from the point of view of the bodies that set the standards, related regulations, country needs and legal basis in each country. This research is limited to the literature to compare Government Accounting Standards in various European countries and Indonesia. Future research can compare Government Accounting Standards in Asia, especially Southeast Asia, because the structure of government in Asia is almost similar in terms of progress and governance structure.